A correlation giving improved description of the capacity and efficiency of vane‐type gas–liquid separators. Issue 5 (20th February 2019) - Dries, Huub W.; Hoffmann, Alex C.
Abstract: Vane‐type demisters are attractive droplet separators because they combine robustness and sufficient separation efficiency with a low‐pressure drop, a high capacity and some fouling resistance. Experience shows that their optimal operation is close to the maximum capacity point and even that at this point the separation efficiency is better at higher pressures. This article proposes a generalized expression this point, as a function of gas and liquid flow and properties, drawing on knowledge about other, related, unit operations, namely cyclone separators and distillation towers. The generalized expression relates the dimensionless velocity with the Archimedes number and a flow parameter. The expression builds on earlier work on a criterion for the inception of droplet entrainment in two‐phase film flow, pioneered by Ishii and Grolmes, and is supported by considerable experimental work published over the last 50 years.